The Relationship Between Interest and History Learning Outcomes of Grade X Students at State High School 2 Palu City - Moh.Rizky; Lukman; Windayanti; Ismail (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The issues raised include the condition of interest in learning history, the process of achieving history learning outcomes, and the relationship between interest and learning outcomes. This study aims to determine the relationship between interest in learning and learning outcomes in History in class X students at State High School 2 Palu City. This study uses a quantitative method through a correlational framework, focusing on the entire class X population of 144 students at State High School 2 Palu City, with a sample of 36 people selected randomly. Data collection was carried out using observations, questionnaires, and tests, while the analysis was carried out descriptively and inferentially, with hypothesis testing carried out through t-tests and Product Moment calculations. The results of the study showed a strong correlation (r = 0.836) between student interest and History achievement, with a t-value of 8.894 exceeding the critical value of 1.691, thus indicating a significant relationship in class X at State High School 2 Palu City.